Influence of atrial fibrillation on efficacy and safety of omecamtiv mecarbil in heart failure: the GALACTIC-HF trial. (23rd March 2022) - Solomon, Scott D; Claggett, Brian L; Miao, Zi Michael; Diaz, Rafael; Felker, G Michael; McMurray, John J V; Metra, Marco; Corbalan, Ramon; Filippatos, Gerasimos; Goudev, Assen R; Mareev, Viatcheslav; Serpytis, Pranas; et al.
Abstract: Aims: In GALACTIC-HF, the cardiac myosin activator omecamtiv mecarbil compared with placebo reduced the risk of heart failure events or cardiovascular death in patients with heart failure with reduced ejection fraction. We explored the influence of atrial fibrillation or flutter (AFF) on the effectiveness of omecamtiv mecarbil. Methods and results: GALACTIC-HF enrolled patients with New York Heart Association (NYHA) Class II–IV heart failure, left ventricular ejection fraction ≤35%, and elevated natriuretic peptides. We assessed whether the presence or absence of AFF, a pre-specified subgroup, modified the treatment effect for the primary and secondary outcomes, and additionally explored effect modification in patients who were or were not receiving digoxin. Patients with AFF ( n = 2245, 27%) were older, more likely to be randomized as an inpatient, less likely to have a history of ischaemic aetiology or myocardial infarction, had a worse NYHA class, worse quality of life, lower estimated glomerular filtration rate, and higher N-terminal pro-B-type natriuretic peptide. The treatment effect of omecamtiv mecarbil was modified by baseline AFF (interaction P = 0.012), with patients without AFF at baseline deriving greater benefit. The worsening of the treatment effect by baseline AFF was significantly more pronounced in digoxin users than in non-users (interaction P = 0.007); there was minimal evidence of effect modification in those patients not using digoxin ( P = 0.47) or in digoxin users not in AFF. Conclusion: Patients in AFF at baseline were less likely to benefit from omecamtiv mecarbil than patients without AFF, although the attenuation of the treatment effect was disproportionally concentrated in patients with AFF who were also receiving digoxin. Clinical Trial Registration: NCT02929329 Structured Graphical Abstract: Structured Graphical abstract In GALACTIC-HF, patients with atrial fibrillation or flutter (AFF) at baseline derived less benefit from Omecamtiv Mecarbil than patients not in AFF. This finding was primarily driven by those patients in AFF who were taking digoxin.